POSTMODERNISM AS A HISTORICAL AND PHILOSOPHICAL PROJECT OF MODERNITY - SOGHOMONYAN, GAGIK (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
The article is devoted to the consideration of the phenomena of personality and history in the post-modernism tradition. The author follows the dynamics of the views about the social history of such philosophers as J.F. Lyotard, M. Foucault, R. Barthes, G. Deleuze, J. Baudrillard from the point of correlation between interpretations of history and the problem of Man.